MICROPROPAGATION OF RAUVOLFIA TETRAPHYLLA L. FROM IN VITRO SEEDLING DERIVED EXPLANTS USING VARIOUS AMINO ACIDS - Anitha S. (Journal of Animal and Plant Sciences, 2023)
Rauvolfia tetraphylla L. belonging to the family Apocynaceae has been used in the treatment of hypertension, snake bites and insect sting poisons since a long time. Though various attempts were reported for the regeneration of R. tetraphylla through explants collected from in vivo grown plants, this is the first attempt reporting regeneration from in vitro seedling derived explants. Various amino acids were also tested for their efficacy on in vitro regeneration of R. tetraphylla. The regeneration through the shoot tip and cotyledonary node explants of in vitro grown seedlings were achieved in MS+B5 medium fortified with 3% sucrose and 0.8% agar. By adjusting the cytokinin (BA (Benzyl adenine), KN (Kinetin)) concentrations and various amino acids (glutamine, lysine, proline, methionine and isoleucine) in multiple shoot induction medium, the media composition was optimized for obtaining maximum results. Compared to KN, BA gave best response for multiple shoot induction. Maximum number of shoots were produced in the cotyledonary nodes than the shoot tips. Amino acids encouraged multiple shoot induction (especially glutamine and proline) response when combined with 4.44 µM BA, where 34.75 and 29.18 shoots were produced per explant with 0.51 mM glutamine and 0.66 mM proline respectively. Elongation of shoots was 100 % on medium with 0.44 µM BA and 1.156 µM GA3 (Gibberellic acid). The rooting of elongated shoots (65%) was attained by incorporating IBA (Indole butyric acid) in the medium. The roots were thick, long, about 4.8 roots were produced per explant on medium supplied with 9.84 µM IBA. The hardening and field introduction attempts were successful with the survival rate of 78 % after 12 weeks of acclimatization.
Keywords: Cotyledonary node; amino acids; shoot tip; micropropagation